Prevalence of Cozen's Phenomenon of the Proximal Tibia. Issue 6 (July 2019) - Yang, Brian W.; Shore, Benjamin J.; Rademacher, Emily; May, Collin; Watkins, Colyn J.; Glotzbecker, Michael P.
Abstract : Background: There has been little investigation into the epidemiology of Cozen's phenomenon, genu valgum as a complication of proximal tibial metaphysis fractures. In this study, we present a large case series of proximal tibia fractures in children to describe the prevalence, epidemiology, and characteristics associated with Cozen's phenomenon following proximal tibial fracture in children. Methods: We searched the orthopedic database at our institution for all patients aged 1 to 8 years old with proximal tibia fractures presenting for initial fracture management between January 1, 2014 and December 31, 2017. Demographic data, mechanism of injury, fracture characteristics, and the presence of a concurrent fibula fracture were determined from the medical records. Initial and follow-up valgus angulation was measured as the angle between a line perpendicular to the proximal tibial physis and a line drawn along the axis of the tibia. Differences in the rate of valgus angulation by mechanism of injury and fracture type were compared. Results: In total, 181 fractures in 181 patients were included in our study (98 male, 83 female). The average age at injury was 4.55 years (range, 1.02 to 7.95 y); 140 patients (77.3%, 140/181) had initial valgus angulation of <4 degrees; 20 of these patients (14.3%, 20/140) developed angulation of at least 4 degrees at some point during follow-up at an average of 0.8 months (range, 0.2 to 1.9 mo); 4 patients (20.0%, 4/20) with <4 degrees of initial angulation had persistent valgus angulation of 5 degrees at latest follow-up. Two of these patients were not scheduled to return because the provider did not determine the valgus angulation to be clinically meaningful. The 2 other patients were asymptomatic and continued to receive nonoperative management. No patients in our series required surgical correction of valgus deformity. Conclusions: Cozen's phenomenon is an uncommon complication of proximal tibial metaphysis fractures. Eliminating unnecessary radiographs and clinical visits for our pediatric trauma patients will improve the quality and value of care delivery. Level of Evidence: Level IV.